2009
DOI: 10.1007/s11832-009-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

Axial STIR MRI: A faster method for confirming femoral head reduction in DDH

Abstract: While not indicated in all cases of femoral head dislocation, MRI is useful to confirm concentric reduction of the femoral head in a dysplastic acetabulum when examination under anaesthesia and radiographic screening have been uncertain. In our series, 1 in 20 cases needed MRI. This is a reliable, non-invasive method confirming definite reduction of the femoral head prior to discharge in all of our patients. In this initial series, all patients had axial and coronal STIR and proton density MRI. We now only use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…The sequences are completed within 5 minutes. TIRM offers excellent definition of the cartilaginous acetabulum and femoral head an allows assessment of their relationship to one another [9]. In our study TIRM images were found to be useful mainly in coronal planes.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The sequences are completed within 5 minutes. TIRM offers excellent definition of the cartilaginous acetabulum and femoral head an allows assessment of their relationship to one another [9]. In our study TIRM images were found to be useful mainly in coronal planes.…”
Section: Discussionmentioning
confidence: 60%
“…Conroy et al [9] found that STIR (Short TI Inversion Recovery) or TIRM (Turbo-Inversion Recovery-Magnitude) imaging in axial planes provided adequate information regarding the position of the femoral head relative to the acetabulum. The sequences are completed within 5 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention should be given to contrast medium concentration and to avoid extravasation or causing damage to vasomotor nerves during needle placement 6 . The radiation load should be considered when requesting CT 1,7,8 . Although MRI is not regularly used in DDH, its indications are increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvi pedal alçıdaki kalçanın redüksiyonunu doğrulamak için MR ve ultrasonografi de kullanılabilir. [61,62] Perfüzyonlu MR görüntüleme çalışmaları, ameliyat sonrası alçıdaki femur başı damarlanmasını belirlemeye de olanak tanıyacaktır. [63] Altı hafta sonra, kalça hasta anestezi altında iken muayene edilir ve eğer redüksiyon tatmin edici ise ikinci bir alçı uygulanır.…”
Section: Anteri̇or Açik Redüksi̇yonunclassified